Herstellung und Charakterisierung von Wood-Plastic-Composites (WPC) mit einer Matrix aus thermoplastischen Polyurethanen zur Erzeugung einer Holz-WPC-Verbundstruktur - Richters, Maximilian

Herausforderungen in der inklusiven Mädchenarbeit: Begleitforschung der „Inklusiven anonymen Zuflucht“ des Mädchenhaus Bielefeld e.V. - Richter, Susanne (Inklusiver Kinderschutz – Anforderungen, Herausforderungen, Perspektiven)

Der Imperativ der Biographisierung und die Ambivalenzen individueller Verantwortungszuschreibung - Dahmen, Stephan (Responsibilisierung)

"Das Berufsfeldpraktikum empfinde ich als nicht notwendig im Studium" - Evaluationsergebnisse zum Berufsfeldpraktikum aus Sicht von Lehramtsstudierenden - Meier, Jana; Vogelsang, Christoph; Rotärmel, Tanja (Das Berufsfeldpraktikum als Professionalisierungselement - Grundlagen, Konzepte, Beispiele für das Lehramtsstudium)

Sinnvolle Ergänzung oder bewusster Bruch? - Tätigkeitsfelder im Berufsfeldpraktikum innerhalb des Lehramtsstudiums - Vogelsang, Christoph; Meier, Jana (Das Berufsfeldpraktikum als Professionalisierungselement - Grundlagen, Konzepte, Beispiele für das Lehramtsstudium)

Mediennutzung von Jugendlichen zu sozialen und politischen Fragen, schulische Aktivitäten und Lehrkräftefortbildungen - Welsandt, N.J.; Huschle, L.; Drossel, Kerstin; Deimel, D.; Abs, H.J. (ICCS 2022. Schulische Sozialisation und politische Bildung von 14-Jährigen im internationalen Vergleich)

Soziologie des Flitzers - Riedl, Lars (Kölner Zeitschrift für Soziologie und Sozialpsychologie)

"Das Berufsfeldpraktikum empfinde ich als nicht notwendig im Studium" - Evaluationsergebnisse zum Berufsfeldpraktikum aus Sicht von Lehramtsstudierenden - Meier, Jana; Vogelsang, Christoph; Rotärmel, Tanja (Das Berufsfeldpraktikum als Professionalisierungselement. Grundlagen, Konzepte, Beispiele für das Lehramtsstudium)

Pyroelectric influence on lithium niobate during the thermal transition for cryogenic integrated photonics - Thiele, Frederik; Hummel, Thomas; Lange, Nina Amelie; Dreher, Felix; Protte, Maximilian; Bruch, Felix vom; Lengeling, Sebastian; Herrmann, Harald; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Materials for Quantum Technology)
Abstract Lithium niobate has emerged as a promising platform for integrated quantum optics, enabling efficient generation, manipulation, and detection of quantum states of light. However, integrating single-photon detectors requires cryogenic operating temperatures, since the best performing detectors are based on narrow superconducting wires. While previous studies have demonstrated the operation of quantum light sources and electro-optic modulators in LiNbO 3 at cryogenic temperatures, the thermal transition between room temperature and cryogenic conditions introduces additional effects that can significantly influence device performance. In this paper, we investigate the generation of pyroelectric charges and their impact on the optical properties of lithium niobate waveguides when changing from room temperature to 25 K, and vice versa. We measure the generated pyroelectric charge flow and correlate this with fast changes in the birefringence acquired through the Sénarmont-method. Both electrical and optical influence of the pyroelectric effect occur predominantly at temperatures above 100 K.
Keywords: General Earth and Planetary Sciences; General Environmental Science

„4 THe BoYZ“ – Widmungen im Szene-Graffiti aus konstruktionsgrammatischer Perspektive. Die multimodale Relator-Konstruktion als grammatische Musterbildung im Horizont des Textes - Tophinke, Doris; Dübbert, Alexander (Konstruktionsgrammatik X. Textsorten und Textmuster als Konstruktionen?)

Perspectives of children and young people on their education as preparing for their future in the digital age: In-depth qualitative study in five European countries. - Eickelmann, Birgit; Barbovschi, M.; Holmarsdottir, H.B.; Parsanoglou, D.; Sisask, M.; Labusch, Amelie (Understanding the everyday digital lives of children and young people)

Untersuchung des Füllverhaltens holzfaserverstärkter Kunststoffe (WPC) mit hohen Füllstoffgehalten - Flachmann, Felix

Simulationsgestützte Bestimmung und Optimierung der Mischgüte in der Einschneckenextrusion - Frank, Maximilian

Alexandra Treder (Universität Paderborn) rezensiert: Döll, Marion & Michalak, Magdalena (2023): Deutsch als Zweitsprache und inklusive Bildung. [Deutsch als Zweitsprache – Positionen, Perspektiven, Potenziale, Bd. 3]. Münster: Waxmann, 142 Seiten. ISBN 978-3-8309-4711-0. - Treder, Alexandra (Forschungsportal für Spracherwerb und Migration (daz-portal))

Digitalisierungsbezogene Lehrkräftebildung als Gegenstand internationaler Schulleistungsstudien - Domke, Marius; Fröhlich, Nadine; Eickelmann, Birgit; Pink, Sara (Lehrkräftebildung in der digitalen Welt – zukunftsorientierte Forschungs- und Praxisperspektiven)

Supporting Error Chains in Static Analysis for Precise Evaluation Results and Enhanced Usability - Wickert, Anna-Katharina; Schlichtig, Michael; Vogel, Marvin; Winter, Lukas; Mezini, Mira; Bodden, Eric
Context Static analyses are well-established to aid in understanding bugs or vulnerabilities during the development process or in large-scale studies. A low false-positive rate is essential for the adaption in practice and for precise results of empirical studies. Unfortunately, static analyses tend to report where a vulnerability manifests rather than the fix location. This can cause presumed false positives or imprecise results. Method To address this problem, we designed an adaption of an existing static analysis algorithm that can distinguish between a manifestation and fix location, and reports error chains. An error chain represents at least two interconnected errors that occur successively, thus building the connection between the fix and manifestation location. We used our tool CogniCryptSUBS for a case study on 471 GitHub repositories, a performance benchmark to compare different analysis configurations, and conducted an expert interview. Result We found that 50 % of the projects with a report had at least one error chain. Our runtime benchmark demonstrated that our improvement caused only a minimal runtime overhead of less than 4 %. The results of our expert interview indicate that with our adapted version participants require fewer executions of the analysis. Conclusion Our results indicate that error chains occur frequently in real-world projects, and ignoring them can lead to imprecise evaluation results. The runtime benchmark indicates that our tool is a feasible and efficient solution for detecting error chains in real-world projects. Further, our results gave a hint that the usability of static analyses may benefit from supporting error chains.
Keywords: Static analysis; error chains; false positive re- duction; empirical studies

Children and young people’s ICT experiences in school education: Participatory research design to engage children and young people as experts in research - Labusch, Amelie; Eickelmann, Birgit; Casamassima, Gianna; Drossel, Kerstin; Gudmundsdottir, G.B.; Kazani, A.; Mifsud, L.; Symeonaki, M.; Teidla-Kunitsõn, G. (Understanding the everyday digital lives of children and young people)

Videoanalysen zu unterrichtlichen Lehr- und Lernprozessen unter den Bedingungen der Digitalität an organisational resilienten Schulen in Deutschland - Drossel, Kerstin; Oldak, Anna; Bette, Ricarda; Eickelmann, Birgit; Schreyer, P. (Lehrkräftebildung in der digitalen Welt – zukunftsorientierte Forschungs- und Praxisperspektiven)

From Swiss-cheese to discrete ferroelectric composites: assessing the ferroelectric butterfly shape in polarization loops - Myroshnychenko, Viktor; Mulavarickal Jose, Pious Mathews; Farheen, Henna; Ejaz, Shafaq; Brosseau, Christian; Förstner, Jens (Physica Scripta)
We explore the polarization hysteretic behaviour and field-dependent permittivity of ferroelectric-dielectric 2D materials formed by random dispersions of low permittivity inclusions in a ferroelectric matrix, using finite element simulations. We show how the degree of impenetrability of dielectric inclusions plays a substantial role in controlling the coercive field, remnant and saturation polarizations of the homogenized materials. The results highlight the significance of the degree of impenetrability of inclusion in tuning the effective polarization properties of such ferroelectric composites: coercive field drops significantly as percolation threshold is attained and remnant polarization decreases faster than a linear decay.
Keywords: tet_topic_ferro

Edge-Connectivity and Pairwise Disjoint Perfect Matchings in Regular Graphs - Ma, Yulai; Mattiolo, Davide; Steffen, Eckhard; Wolf, Isaak Hieronymus (Combinatorica)
For 0 ≤ t ≤ r let m(t, r) be the maximum number s such that every t-edge-connected r-graph has s pairwise disjoint perfect matchings. There are only a few values of m(t, r) known, for instance m(3, 3) = m(4, r) = 1, and m(t, r) ≤ r − 2 for all t = 5, and m(t, r) ≤ r − 3 if r is even. We prove that m(2l, r) ≤ 3l − 6 for every l ≥ 3 and r ≥ 2l.
Keywords: Computational Mathematics; Discrete Mathematics and Combinatorics